Subcycle resolved strong field ionization of chiral molecules and the origin of chiral photoelectron asymmetries - M. Hofmann; D. Trabert; A. Geyer; N. Anders; J. Kruse; J. Rist; L. Ph. H. Schmidt; T. Jahnke; M. Kunitski; M. S. Schöffler; S. Eckart; R. Dörner (Physical Review Research)
We report on strong field ionization of S- and R-propylene oxide in circularly polarized two-color laser fields. We find that the relative helicity of the two single-color laser fields affects the photoelectron circular dichroism (PECD). Further, we observe that PECD is modulated as a function of the subcycle release time of the electron. Our experimental observations are successfully described by a heuristic model based on electrons in chiral initial states, which are selectively liberated by the laser field and, after tunneling, interact with an achiral Coulomb potential.